Single‐molecule tracking reveals that the nucleoid‐associated protein HU plays a dual role in maintaining proper nucleoid volume through differential interactions with chromosomal DNA. Issue 1 (3rd August 2020) - Bettridge, Kelsey; Verma, Subhash; Weng, Xiaoli; Adhya, Sankar; Xiao, Jie
Abstract: HU (Histone‐like protein from Escherichia coli strain U93) is the most conserved nucleoid‐associated protein in eubacteria, but how it impacts global chromosome organization is poorly understood. Using single‐molecule tracking, we demonstrate that HU exhibits nonspecific, weak, and transitory interactions with the chromosomal DNA. These interactions are largely mediated by three conserved, surface‐exposed lysine residues (triK), which were previously shown to be responsible for nonspecific binding to DNA. The loss of these weak, transitory interactions in a HUα(triKA) mutant results in an over‐condensed and mis‐segregated nucleoid. Mutating a conserved proline residue (P63A) in the HUα subunit, deleting the HUβ subunit, or deleting nucleoid‐associated naRNAs, each previously implicated in HU's high‐affinity binding to kinked or cruciform DNA, leads to less dramatically altered interacting dynamics of HU compared to the HUα(triKA) mutant, but highly expanded nucleoids. Our results suggest HU plays a dual role in maintaining proper nucleoid volume through its differential interactions with chromosomal DNA. On the one hand, HU compacts the nucleoid through specific DNA structure‐binding interactions. On the other hand, it decondenses the nucleoid through many nonspecific, weak, and transitory interactions with the bulk chromosome. Such dynamic interactions may contribute to the viscoelastic properties and fluidity of the bacterial nucleoid to facilitate proper chromosome functions. Abstract : The most conserved chromosome‐associated protein in bacteria, HU, has two roles in maintaining a proper chromosome volume: (1) condensation, mediated by HU's high‐affinity binding to looped or bent DNA, and (2) expansion, mediated by the sum of multiple weak and transitory interactions of HU with linear DNA.